I2 Immunisation – one of medicine's greatest successes. (12th March 2018) - Elliman, D
Abstract : According to WHO, immunisation is second only to clean water as of benefit to child health. The history of immunisation in UK goes back almost 300 years with the introduction of smallpox inoculation. Almost 100 years later Edward Jenner published his work on smallpox vaccination using cowpox. Pasteur produced vaccines against anthrax and rabies, but these were only seldom used and it wasn't until the first half of the 20th century that the next vaccine (diphtheria) was brought into universal use. Since then, the number of vaccines in the universal programme has risen almost exponentially. In UK, vaccination against 13 diseases in addition to meningococcal A, B, C, W and Y, is offered routinely to all children (HPV to males only). Worldwide, immunisation is a priority for national governments, the World Health Organisation and Non-Governmental Organisations. All countries have an immunisation programme though financial resources may limit the vaccines that less well-resourced countries can employ. Smallpox has been eradicated and polio is on the retreat with only 21 cases reported in 2017. While overall, the story of immunisation is a great success, there have been, and continue to be, a number of obstacles have hampered the attainment of its full potential. Different scares (e.g. MMR and autism in UK, mercury and autism in USA and hepatitis B and multiple sclerosis in France) have meant falls in uptake, and, in some countries, vaccination workers have been murdered. Unfortunately, social media does not only allow information to spread rapidly, but also misinformation. Twitter dos not allow for rational conversation, more name calling and didactic statements which often serve only to further people's views, however misguided. Unfortunately, the credibility of an immunisation programme can be destroyed overnight, while it may take years to build it up again. Fortunately, the overwhelming majority of parents are in favour of immunisation, however in some countries, immunisations rates are so low that vaccine preventable diseases are still relatively common and avoidable deaths occur. Governments have turned to compulsion in one form or another. This is a highly controversial measure and not one that is envisaged in UK.